Sistem Informasi Penjualan Barang Elektronik pada Toko Elektronik Rahman - Nelly Agustina Purba; Marlyna Infryanti Hutapea; Rena Nainggolan (Universitas Methodist Indonesia, 2024)
This research aims to overcome challenges in the sales process at Rahman Electronic Store through the development of a web-based electronic sales information system. This research also aims to improve the product marketing strategy at the store. This sales information system is expected to be able to produce reports quickly and provide convenience in accessing information about products available at Toko Rahman.The research methods used include literature study, field research through observation, and interviews with shop owners and employees, as well as system analysis. The system design includes the creation of data flow diagrams, database structures, output design, and programming. The result of this research is the development of a web-based electronic goods sales information system that facilitates the process of selling products online through the Rahman Electronic Store website.Some of the main findings from this study include: A web-based sales information system assists Rahman Electronic Store in managing product information and sales transactions efficiently. The product management system provided by this system allows shop owners to easily manage product stock and prices. This system also provides sales displays, product orders, and payment processes that make it easier for customers to shop. With the existence of a web-based sales information system, it is expected that Rahman Electronic Store can increase the efficiency of the sales process and provide a better shopping experience for customers.